Strategies for Restoration of Soil Quality to Mitigate Land Degradation in Semi-Arid North Western Nigeria - Raji, B A (Annals of Arid Zone, 2019)
Soil degradation alone was reportedly estimated to affect approximately 485 million Africans, with annual long-term costs of between US 95-279 billion. Increasing agricultural productivity in Nigeria, with its over 70% marginal/problem land and a decreasing per capital arable land (PCAL), would, therefore, need sound and adequate information on soil quality enhancement. Soil organic carbon (SOC) plays a crucial role in influencing physical, chemical and biological properties, and the overall soil quality. Some common strategies for restoration of SOC include conservation tillage which reduces decomposition, fallow, agroforestry, improved pasture and optimal fertilization which improves C levels through enhanced biomass production. After 6 years of natural fallow, the un-amended soils in the Samaru experiment recorded slight decrease in soil organic matter (SOC) content from 7.04 t C ha-1 to 6.83 t C ha-1 representing about 3% reduction. This result shows that the resilient power of the un-amended soils (degraded) to selfrestoration is low under natural fallow. The potential for carbon sequestration by the use of eucalyptus (Eucalyptus globulus) and neem (Azadirachta indica) trees in afforestation in NW Nigeria is about 23 g C m-2 yr-1 to 305 g C m-2 yr-1 over rates in unstabilized sand dune (control). These values would increase substantially if management practices such as fertilization are introduced. The use of NPK between 1977 and 1995, a period of 18 years in the Samaru experiment, improved SOC content from 4.95 t C ha-1 to 7.30 t C ha-1, reflecting a rate of 13 g C m-2 yr-1. This rate is about 50% less the rate using manure alone and 75% less using manure with NPK. The use of N fertilization alone for 18 years also resulted in an increase of about 2.83 t C ha-1 or 16 g C m-2 yr-1. In the NE Nigeria, the use of manure along with the selected restorative strategies gave the fastest options for restoring soil quality and productivity. Key words: Land degradation, soil organic matter, soil quality, biomass production.